Primary magnetic resonance imaging/ultrasonography fusion‐guided biopsy of the prostate. (17th April 2018) - Maxeiner, Andreas; Kittner, Beatrice; Blobel, Conrad; Wiemer, Laura; Hofbauer, Sebastian L.; Fischer, Thomas; Asbach, Patrick; Haas, Matthias; Penzkofer, Tobias; Fuller, Florian; Miller, Kurt; Cash, Hannes
Abstract : Objective: To examine the performance of a primary magnetic resonance imaging (MRI)/ultrasonography (US) fusion‐guided targeted biopsy (TB), and in combination with an added systematic biopsy (SB). Patients and Methods: Analysis of 318 consecutive biopsy‐naïve men with suspicious multiparametric MRI (mpMRI; Prostate Imaging Reporting and Data System [PI‐RADS] score ≥3) undergoing transrectal TB and 10‐core SB between January 2012 and December 2016. The indication for performing mpMRI was based on clinical parameters and decided by the treating urologist before admission. TB was performed with a sensor‐based MRI/US fusion‐guided platform. Clinically significant prostate cancer was defined as Gleason score ≥4 + 3 = 7 (International Society of Urological Pathology Grade [ISUP] grade 3) or maximum cancer core length of ≥6 mm. Results: A median (interquartile range) of 14 (13–14) biopsies per case were taken. The overall cancer detection rate (CDR) was 77% (245/318). The TB alone detected 67% of prostate cancers and the SB alone detected 70%. The PI‐RADS dependent CDR for the combination of TB/SB were 38% (21/55), 78% (120/154) and 95% (104/109) for PI‐RADS scores of 3/4/5, respectively. Clinically significant prostate cancer was diagnosed by the combination of TB and SB in 195 men (61%) and by TB alone in 163 cases (51%). The number of missed or underestimated prostate cancers with a Gleason score ≥8 for TB alone was 31 (10%, P < 0.001) and 21 (7%, P < 0.001) for SB alone in comparison with the results of the combination of TB and SB. The rate of insignificant prostate cancer was comparable for the combination of TB and SB and TB alone (50/318, 16% vs 50/318, 16%). Conclusions: Pre‐biopsy mpMRI is of incremental value in increasing the detection of clinically significant prostate cancer in biopsy‐naïve patients with suspicion of prostate cancer. Combining TB with SB further improved the diagnostic accuracy without increasing the rate of insignificant prostate cancer.